2018
DOI: 10.1371/journal.pone.0195443
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in the global adult HIV-infected population: A systematic review and meta-analysis

Abstract: IntroductionThe widespread use of antiretroviral therapies (ART) has increased life expectancy in HIV patients, predisposing them to chronic non-communicable diseases including Chronic Kidney Disease (CKD). We performed a systematic review and meta-analysis (PROSPERO registration number CRD42016036246) to determine the global and regional prevalence of CKD in HIV patients.MethodsWe searched PubMed, Web of Science, EBSCO and AJOL for articles published between January 1982 and May 2016. CKD was defined as estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
129
5
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 122 publications
(156 reference statements)
9
129
5
13
Order By: Relevance
“…Globally, for example, HIV-related CKD is most prevalent in Africa, with prevalence rates of 7.9%. 9 Furthermore, within the African continent, the prevalence of HIV-related CKD is highest within the West African subregion at 14.6% compared with Southern Africa, which has estimated rates of 3.2%. 9 CKD in LMICs tends to occur earlier and appears to be more severe.…”
Section: Ckd In Lmicsmentioning
confidence: 99%
“…Globally, for example, HIV-related CKD is most prevalent in Africa, with prevalence rates of 7.9%. 9 Furthermore, within the African continent, the prevalence of HIV-related CKD is highest within the West African subregion at 14.6% compared with Southern Africa, which has estimated rates of 3.2%. 9 CKD in LMICs tends to occur earlier and appears to be more severe.…”
Section: Ckd In Lmicsmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis estimated the pooled prevalence of CKD [estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 ] in PLWH in North America to range from a low of 6.5% [95% confidence interval (CI) 4.9–8.5%] using the Cockcroft–Gault (C‐G) formula to a high of 7.4% (95% CI 6.0–9.1%) using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) formula . Studies based on varying levels of GFR reduction and proteinuria have suggested that CKD prevalence in PLWH may be as high as 33% .…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, treatment with an erythropoiesis-stimulating agent or iron, results in increased circulating immature RBCs that have a shorter glycaemic exposure time for glycation to occur, resulting in reduced HbA1c levels, with no significant change in mean glucose levels [10]. There are also several other diseases, prevalent in Africa, that affect the clinical utility of HbA1c and for which alternative markers may be necessary, including sickle-cell disease in the more endemic malaria prone regions, as well as HIV/AIDS and tuberculosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Fructosamine and GA have shorter half-lives than HbA1c, thus reflecting very recent (1-3 weeks) glycaemic control [16], potentially lessening the confounding effect of shortened RBC survival or high RBC turnover. However, the effect of CKD on the agreement between these indices of glycaemic control has yet to be assessed in the African context; where there is a high frequency of factors affecting HbA1c [11,12].…”
Section: Introductionmentioning
confidence: 99%